Preparation and Characterization of Bimetallic Cu-Ni and/or Ni-Cu core-shell Nanoparticles with High Photocatalytic Activity - Phinjaroenphan, Rarm; Boonserm, Kornkanok; Rattanasuporn, Surachet (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 2 (2021): April-June 2021, 2020)
One-pot synthesis of bimetallic Cu-Ni and/or Ni-Cu core-shell nanoparticles have been synthesized by aqueous reduction process, which was very simple, convenient, and prepared under ambient condition. The core-shell system of Cu and Ni could be formed by injecting copper nitrate into an aqueous mixed solution that contained sodium citrate, nickel sulfate, and sodium borohydride. In addition, the injecting time of copper nitrate has a huge effect to obtained either Cu-Ni or Ni-Cu core-shell products with various in size of core and shell structures. Hence, in this report, we explored the morphology and structural information of Cu-Ni and/or Ni-Cu core-shell nanoparticles with varied injecting time of copper nitrate such as 1 min, 5 min, and 10 min, respectively. The effect of the copper nitrate injecting time on the nanoparticles size and types of core and shell also investigated. The bimetallic products were characterized by X-ray diffraction (XRD), high resolution transmission electron microscopy (HR-TEM), and Energy Dispersive X-ray Spectrometer (EDS) methods. Beside, we provided information of photocatalytic activity under UV light illumination of the bimetallic nanoparticles. Compared with Ni monometallic nanoparticle, the bimetallic products enhanced the photocatalytic activity. Keywords:  Cu-Ni and/or Ni-Cu core-shell nanoparticles, Ni nanoparticles, bimetallic nanoparticles, aqueous reduction process, photocatalytic activity